3D Structure of Resistin, A Molecule Responsible for Insulin Resistance: An Computational Approach - Prasad Reddy, S.L.N.; Rajesh, K.S.; Asad, Mohammed (Asian Journal of Chemistry, 2010)
Resistin, a unique signaling molecule involved in type 2 diabetes. It is secreted by adipose tissue. The human resistin consists of 108 amino acids. Protoparam and protascale servers are used to access various general properties of resistin. Modeler, a well known homology modeling tool is used to model the tertiary structure of resistin. Quality of the structural models are evaluated by using procheck and verify 3D and the best model is optimized by swissPDB viewer. PSORT and SignalP servers are used to determine localization and signal peptide of resistin, respectively. It is predicted that resistin starts with highly hydrophobic amino acids and has conserved pattern of cysteines at the C-teminal like any other members of FIZZ family. It consistis of both α-helix and β-sheet. It is hypothesized that resistin has N terminal signal sequence with highly hydrophobic amino acids and is localized extracellularly. Hence it may be exerting its action through a surface receptor, which may negatively regulate insulin signaling pathway and cause dibetes.